Exploring the Integration of Technology in Learning Practices: Study of Faculty Candidates - Kawuryan, Sekar Purbarini (Jurnal Prima Edukasia, 2024)
Elementary education master's program students must complete teaching practice to become lecturers in the future. However, how they integrate and employ technology to support their learning practices is still understudied. This research aims to analyse the integration of technology in research and learning practice. This research employed a qualitative approach with a phenomenological type. The research subjects were students participating in research and learning practice programs who were selected purposively. Data collection was carried out through interviews and documentation. Data was analyzed using interactive analysis. Research programs and learning practices were carried out by utilizing technology in planning, implementing and evaluating learning. Technology-based planning can be seen in teaching materials, teaching media, teaching materials and even the preparation of digital- based teaching assessment instruments. Learning is carried out using a variety of digital technologies. Commonly used learning media include PowerPoint, Canva, video and YouTube. Online quiz applications dominate learning assessment. The findings of this research have urgency in finding patterns of technology integration in lectures. This contributes to the potential for further research regarding the development of technological innovation in learning that needs serious attention to be studied.